College students, shared decision making, and the appropriate use of antibiotics for respiratory tract infections: A systematic literature review - Blyer, Kristina; Hulton, Linda (Journal of American college health, 2016)
Objective: This systematic review examines shared decision making to promote the appropriate use of antibiotics for college students with respiratory tract infections. Participants/Methods: CINAL, Cochrane, PubMed, EBSCO, and PsycNET were searched in October 2014 using the following criteria: English language, human subjects, peer-reviewed, shared decision making for respiratory tract infections, adult patients or college students, and antibiotic use for respiratory tract infections. Twelve articles were selected for final review. Results: College students and younger, more educated, adults prefer shared decision making. Shared decision making shows promise for decreasing antibiotic use for respiratory tract infections. Education, understanding, and provider-patient communication are important to the shared decision-making process. Conclusions: Shared decision making shows promise to promote the appropriate use of antibiotics for respiratory tract infections in college students and could be considered for future studies.